Parafascicular Thalamic and Orbitofrontal Cortical Inputs to Striatum Represent States for Goal-Directed Action Selection - Stayte, Sandy; Dhungana, Amolika; Vissel, Bryce; Bradfield, Laura A. (Frontiers in Behavioral Neuroscience, 2021)
Several lines of evidence accrued over the last 5-10 years have converged to suggest that the parafascicular nucleus of the thalamus and the lateral orbitofrontal cortex each represent or contribute to internal state/context representations that guide action selection in partially observable task situations. In rodents, inactivations of each structure have been found to selectively impair performance in paradigms testing goal-directed action selection, but only when that action selection relies on state representations. Electrophysiological evidence has suggested that each structure achieves this function via inputs onto cholinergic interneurons (CINs) in the dorsomedial striatum. Here we briefly review these studies, then point to anatomical evidence regarding the afferents of each structure and what they suggest about the specific features that each contribute to internal state representations. Finally, we speculate as to whether this role might be achieved interdependently through direct PFOFC projections, or through the convergence of independent direct OFC and PF inputs onto striatal targets.